2019
DOI: 10.1042/bsr20182328
|View full text |Cite
|
Sign up to set email alerts
|

Octamer binding transcription factor-4 expression is associated with cervical cancer malignancy and histological differentiation: a systematic review and meta-analysis

Abstract: Objective: In this work, the relationship between octamer binding transcription factor 4 (OCT-4) expression and the clinicopathological features of cervical cancer (CC) is evaluated in detail. Methods: The library databases Pubmed, Embase, Cochrane library, Wan Fang and Chinese National Knowledge Infrastructure (CNKI) were searched for research related to these concepts published from the time the databases were established until May 2018. The obtained studies are screened, extracted, and evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Likewise, our work shows increased expression of the intestinal oncofetal protein OCT4 in tumors with some degree of undifferentiation (moderately and poorly differentiated), which could lead to progression and even metastasis in RC, considering that it has been reported that the level of stem cell protein expression may be related to the content of these cells in the tumor and suggests its aggressiveness according to the degree of histological differentiation [39]. Similar observations to our data have been described in RC [19], in a case report of CRC [40], as well as in cervical tumors [41] and gastric cancer [8], which could indicate the role of this cell subpopulation in the loss of colonic identity and poorer prognosis [42].…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, our work shows increased expression of the intestinal oncofetal protein OCT4 in tumors with some degree of undifferentiation (moderately and poorly differentiated), which could lead to progression and even metastasis in RC, considering that it has been reported that the level of stem cell protein expression may be related to the content of these cells in the tumor and suggests its aggressiveness according to the degree of histological differentiation [39]. Similar observations to our data have been described in RC [19], in a case report of CRC [40], as well as in cervical tumors [41] and gastric cancer [8], which could indicate the role of this cell subpopulation in the loss of colonic identity and poorer prognosis [42].…”
Section: Discussionsupporting
confidence: 90%
“…I 2 and Qtests were used to evaluate the heterogeneity of the included research questions. If I 2 <50% and P-test of P > 0.1, it indicates that the studies are homogeneous and a fixed effect model is selected; P < 0.1, indicating that there is heterogeneity between studies, and a random effect model was selected (19,20). To find the sources of heterogeneity, subgroup analyses were used to explore sources of heterogeneity.…”
Section: Methodsmentioning
confidence: 99%
“…The quality of the included studies was assessed using the Newcastle-Ottawa Quality Assessment Scale (NOS). NOS consists of three aspects: selection, comparability, and exposure or outcome; a total score of 9 points, and a total score of ≥6 in the study is considered high quality (19).…”
Section: Quality Evaluationmentioning
confidence: 99%
“…As for cervical cancer, Liu et al [297] found that the aberrant activity of HDAC1 in C-33A cells significantly increases the expression of octamer-binding embryonic transcription factor 4 (Oct4), a prognostic biomarker of various types of malignancies that plays a critical role in maintaining the pluripotency and self-renewal of embryonic stem cells [308][309][310][311]. The contribution of histone deacetylase 1 to the maintenance of stem properties in transformed cells was also shown in a recent study by Yokoi et al [312], where an abnormal HDAC 1 expression profile in the ME180 and CaSki cell lines led to the activation of the Oct4, Nanog, and SOX2 genes that exhibit oncogenic function.…”
Section: Changes In the Intensity Of Histone Acetylation During Oncog...mentioning
confidence: 99%